2016
DOI: 10.1007/s00167-016-4215-x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic visualization and assessment of the anterolateral ligament

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 19 publications
1
24
0
6
Order By: Relevance
“…9 Capo et al performed ultrasonographic evaluation on 10 fresh-frozen cadaveric knees with a 14 MHz linear transducer: ultrasonographic examination did not always correctly locate the origin and insertion of the ALL, and the ALL was often difficult to isolate from the surrounding structures, even at dissection. 10 In this study, the major imaging difficulty was to correctly identify and asses the proximal portion of the ALL; however, the distal portion was reliably identified with US on each cadaver in a similar location, and could be effectively isolated during dissection.…”
Section: Discussionmentioning
confidence: 88%
“…9 Capo et al performed ultrasonographic evaluation on 10 fresh-frozen cadaveric knees with a 14 MHz linear transducer: ultrasonographic examination did not always correctly locate the origin and insertion of the ALL, and the ALL was often difficult to isolate from the surrounding structures, even at dissection. 10 In this study, the major imaging difficulty was to correctly identify and asses the proximal portion of the ALL; however, the distal portion was reliably identified with US on each cadaver in a similar location, and could be effectively isolated during dissection.…”
Section: Discussionmentioning
confidence: 88%
“…In this context, it is important to highlight that all these investigations used (in whole or in part) samples from fresh cadavers 10 , 14 - 16 or studied living individuals through images such as magnetic resonance 15 17 , 18 However, there is no consensus among the results of these studies on the anatomical characteristics of the ALL: 10 , 16 , 19 , 20 while some studies verified the presence of the ALL in most of the samples, 10 , 15 , 16 others did not identify this ligament in even half of the specimens, 21 , 22 and one study show no ALL in their samples 19 . Furthermore, contradictory results exist within the same investigation: Vincent et al 9 identified the ALL of the knee as a capsular structure in individuals during arthroscopic knee surgery, while in its cadaver sample this ligament was found to be intracapsular.…”
Section: Discussionmentioning
confidence: 99%
“…La ultrasonografía es una herramienta de diagnóstico fiable para identificar una estructura hiperecogénica en la zona anterolateral de la rodilla correspondiente al LAL (31)(32)(33) . Además, permite un estudio dinámico de la misma.…”
Section: Ecografíaunclassified
“…La fractura de Segond se puede justificar como una avulsión de este ligamento en su inserción tibial (9,27,28) . La resonancia magnética (RM) (8,(28)(29)(30) y la ecografía (31)(32)(33) están siendo utilizadas para caracterizar este ligamento.Para su tratamiento se dispone de diversas técnicas de refuerzo extraarticular con diferentes tipos de injerto (34)(35)(36)(37) , obteniendo buenos resultados tras un seguimiento de 24 meses (38) . Debido a la gran cantidad de estudios con respecto a este ligamento en los últimos años, se cree conveniente realizar esta revisión bibliográ-fica para definir la incidencia, la anatomía, la biomecánica, la clínica, las pruebas de imagen y el tratamiento del mismo.…”
unclassified